Embryonic-only arsenic exposure in killifish (Fundulus heteroclitus) reduces growth and alters muscle IGF levels one year later - Szymkowicz, Dana B. (Aquat Toxicol, 2017)
Arsenic is a contaminant of drinking water and crops in many parts of the world. Epidemiological studies have shown that arsenic exposure is linked to decreased birth weight, weight gain, and proper skeletal muscle function. The goal of this study was to use killifish (Fundulus heteroclitus) as a model to determine the long-term effects of embryonic-only arsenic exposure on muscle growth and the insulin-like growth factor (IGF) pathway. Killifish embryos were exposed to 0, 50, 200 or 800ppb As(III) from fertilization until hatching. Juvenile fish were reared in clean water and muscle samples were collected at 16, 28, 40 and 52 weeks of age. There were significant reductions in condition factors, ranging from 12–17%, in the fish exposed to arsenic at 16, 28 and 40 weeks of age. However, by 52 weeks, no significant changes in condition factors were seen. Alterations in IGF-1R and IGF-1 levels were assessed as a potential mechanism by which growth was reduced. While there no changes in hepatic IGF-1 transcripts, skeletal muscle cells can also produce their own IGF-1 and/or alter IGF-1 receptor levels to help enhance growth. After a 200 and 800ppb embryonic exposure, fish grown in clean water for 16 weeks had IGF-1R transcripts that were 2.8-fold and 2-fold greater, respectively, than unexposed fish. Through 40 weeks of age, IGF1-R remained elevated in the 200ppb and 800ppb embryonic exposure groups by 1.8–3.9-fold, while at 52 weeks of age, IGF-1R levels were still significantly increased in the 800ppb exposure group. Skeletal muscle IGF-1 transcripts were also significantly increased by 1.9–5.1 fold through the 52 weeks of grow-out in clean by water in the 800ppb embryonic exposure group. Based on these results, embryonic arsenic exposure has long-term effects in that it reduces growth and increases both IGF-1 and IGF-1R levels in skeletal muscle even 1 year after the exposure has ended.